Rancang Bangun Alat Pendeteksi Kebakaran Asap dan Kebocoran Gas Pada Kapal Tugboat Menggunakan IoT - Arwinsyah, Muhammad; Ardhillah, Ahmad; Surojo, Surojo; Sulistyo, Eko (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
Fire, smoke, and gas leak detection systems are among the most influential aspects of security, including on Tugboats. This detection system usually cannot detect in real-time. With the development of Internet of Things (IoT) technology, it is expected to be used for a more accurate and real-time detection system. The purpose of this final project is to create a system that uses the Internet of Things (IoT) as an early warning message in the event of a fire, smoke, and gas leak on a Tugboat. The methodology for completing this final project is data collection and literature study in the initial stages carried out in making hardware with the selection of components used by the function of this final project tool. In the programming process, the radius method is used to detect how far the sensor distance can be detected in detecting using the Internet of Things (IoT) as a warning message in case of fire, smoke, and gas leakage. Thus, this final project produces a fire, smoke, and gas leak detection system in real-time and monitors using a smartphone. This system can be used in various environmental places on the ship, such as the kitchen, capt room, mess room, and command room, to detect early accidents on the Tugboat.